Reorienting health systems to care for people with HIV beyond viral suppression. Issue 12 (December 2019) - Safreed-Harmon, Kelly; Anderson, Jane; Azzopardi-Muscat, Natasha; Behrens, Georg M N; d'Arminio Monforte, Antonella; Davidovich, Udi; del Amo, Julia; Kall, Meaghan; Noori, Teymur; Porter, Kholoud; Lazarus, Jeffrey V
Summary: The effectiveness of antiretroviral therapy and its increasing availability globally means that millions of people living with HIV now have a much longer life expectancy. However, people living with HIV have disproportionately high incidence of major comorbidities and reduced health-related quality of life. Health systems must respond to this situation by pioneering care and service delivery models that promote wellness rather than mere survival. In this Series paper, we review evidence about the emerging challenges of the care of people with HIV beyond viral suppression and identify four priority areas for action: integrating HIV services and non-HIV services, reducing HIV-related discrimination in health-care settings, identifying indicators to monitor health systems' progress toward new goals, and catalysing new forms of civil society engagement in the more broadly focused HIV response that is now needed worldwide. Furthermore, in the context of an increasing burden of chronic diseases, we must consider the shift that is underway in the HIV field in relation to burgeoning policy and programmatic efforts to promote healthy ageing.